Liposomal Delivery of a Biotechnological Lavandula angustifolia Miller Extract Rich in Rosmarinic Acid for Topical Herpes Simplex Therapy - Federica Fulgheri; Fabrizio Angius; Matteo Perra; Ilenia Delogu; Silvia Puxeddu; Milen I. Georgiev; Renáta Novotná; Jana Franková; Misia Lobina; Aldo Manzin; Maria Manconi; Maria Letizia Manca (Antioxidants)
Herpes simplex virus type 1 (HSV-1) is a widespread pathogen responsible for recurrent infections, primarily affecting the skin and mucous membranes. With the aim of targeting both the viral infection and the associated inflammatory response, biotechnologically produced Lavandula angustifolia Miller (L. angustifolia) extract, rich in rosmarinic acid, was incorporated into liposomal formulations intended for topical application. Lavender is known for its strong anti-inflammatory, antioxidant, wound-healing, and antiviral properties. However, its low stability under certain conditions limits its therapeutic potential. Four different formulations were developed: conventional liposomes, glycerosomes, hyalurosomes, and glycerohyalurosomes. The vesicles were characterized for size, stability, and entrapment efficiency. Glycerosomes were the smallest (~58 nm), while the other formulations ranged around 77 nm, all maintaining a highly negative surface charge, ensuring stability and reduced aggregation. Glycerol-containing formulations demonstrated superior stability over 12 months, while liposomes and hyalurosomes increased their size after only two months. Entrapment efficiency reached up to 100% for most vesicles, except for glycerohyalurosomes (~54%). In vitro studies on Normal Human Dermal Fibroblasts (NHDFs) demonstrated that all formulations were biocompatible and enhanced cell viability under oxidative stress. Glycerosomes, hyalurosomes, and glycerohyalurosomes exhibited significant anti-inflammatory activity by reducing MMP-1 and IL-6 levels in LPS-stimulated fibroblasts. Furthermore, these preliminary results highlighted promising antiviral activity against HSV-1 of the obtained formulations, particularly when applied during or post-infection. Overall, these phospholipid vesicles offer a dual therapeutic approach, combining antioxidant, anti-inflammatory, and antiviral effects, positioning them as promising candidates for the treatment of HSV-induced skin lesions and related inflammatory conditions.